2013
DOI: 10.1111/jvim.12180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neutrophil Gelatinase‐Associated Lipocalin as a Marker of Kidney Injury in Dogs

Abstract: Background: Acute kidney injury (AKI) is a common and often fatal disorder in dogs. Hypothesis: Urine neutrophil gelatinase-associated lipocalin (NGAL)/creatinine ratio is a sensitive and specific biomarker of AKI in dogs.Animals: Ninety-four dogs. Methods: Prospective study. Dogs were classified as follows: (1) healthy dogs, (2) dogs with lower urinary tract disorders, (3) dogs with chronic kidney disease (CKD), (4) dogs with azotemic International Renal Interest Society (IRIS) AKI Grades II-V, and (5) dogs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
83
4
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 29 publications
7
83
4
3
Order By: Relevance
“…Studies have demonstrated that NGAL is a useful biomarker in humans with renal disease,3 but the use of NGAL as a marker in dogs with naturally occurring kidney disease has only recently been explored in AKI 28. The results of this study indicated that NGAL is a promising renal biomarker when serum and urine NGAL concentrations in azotemic dogs, especially those with CKD, are evaluated.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Studies have demonstrated that NGAL is a useful biomarker in humans with renal disease,3 but the use of NGAL as a marker in dogs with naturally occurring kidney disease has only recently been explored in AKI 28. The results of this study indicated that NGAL is a promising renal biomarker when serum and urine NGAL concentrations in azotemic dogs, especially those with CKD, are evaluated.…”
Section: Discussionmentioning
confidence: 84%
“…In dogs with naturally occurring kidney disease, the uNGAL‐to‐creatinine ratio has been used to diagnose AKI 28. However, the prognostic role of NGAL in dogs has not been evaluated yet.…”
mentioning
confidence: 99%
“…Urine immunoglobulin G (uIgG) and urine retinol binding protein (uRBP) were increased in dogs with primary CKD7 and those with renal dysfunction secondary to various systemic diseases including pyometra, babesiosis, and snake envenomation 7, 8, 9, 10, 11, 12, 13, 14, 15. Urine, plasma, and serum neutrophil gelatinase‐associated lipocalin (NGAL) and urine N‐acetyl‐β‐D‐glucosaminidase (uNAG), a renal tubular enzyme, are tubular markers increased in both acute and CKD in dogs 7, 11, 12, 15, 16, 17, 18, 19, 20, 21, 22. Neutrophil gelatinase‐associated lipocalin originates not only in the renal tubules but also from neutrophil granules and many other organs 23.…”
mentioning
confidence: 99%
“…Leishmaniasis (Palacio et al 1997) X-linked hereditary nephropathy (Nabity et al 2012) Heartworm disease with cardiac impairment (Uechi et al 1994b) Pyometra Experimental immune complex glomerulonephritis (Bishop et al 1991) Acute renal failure experimentally induced in cats (NAG-B isoenzyme) (Sato et al 2002a) CKD in cats (Jepson et al 2010a) Hypercortisolism Gamma-glutamyl transpeptidase Aminoglycoside-induced nephrotoxicity (Greco et al 1985;Grauer et al 1995;Rivers et al 1996) Renal insufficiency associated with pyometra (De Schepper et al 1989) Heartworm disease with cardiac insufficiency (Uechi et al 1994b) Leishmaniasis (Palacio et al 1997) Envenomation by the common European adder (Palviainen et al 2013) Experimental immune complex glomerulonephritis in cats (Bishop et al 1991) Neutrophil gelatinaseassociated lipocalin Acute kidney injury (Hsu et al 2014a;Segev et al 2013;Zhou et al 2014) Chronic kidney disease (Hsu et al 2014a;Steinbach et al 2014) Retinol binding protein…”
Section: N-acetyl-β-d-glucosaminidasementioning
confidence: 99%